Differences in the clinical and hormonal presentation of patients with familial and sporadic primary aldosteronism - Araujo-Castro, Marta; Parra, Paola; Martín Rojas-Marcos, Patricia; Paja Fano, Miguel; González Boillos, Marga; Pascual-Corrales, Eider; García Cano, Ana María; Ruiz-Sanchez, Jorge Gabriel; Vicente Delgado, Almudena; Gómez Hoyos, Emilia; Ferreira, Rui; García Sanz, Iñigo; et al. (Frontiers in Endocrinology, 2024)
Purpose To compare the clinical and hormonal characteristics of patients with familial hyperaldosteronism (FH) and sporadic primary aldosteronism (PA). Methods A systematic review of the literature was performed for the identification of FH patients. The SPAIN-ALDO registry cohort of patients with no suspicion of FH was chosen as the comparator group (sporadic group). Results A total of 360 FH (246 FH type I, 73 type II, 29 type III, and 12 type IV) cases and 830 sporadic PA patients were included. Patients with FH-I were younger than sporadic cases, and women were more commonly affected (P = 0.003). In addition, the plasma aldosterone concentration (PAC) was lower, plasma renin activity (PRA) higher, and hypokalemia (P < 0.001) less frequent than in sporadic cases. Except for a younger age (P < 0.001) and higher diastolic blood pressure (P = 0.006), the clinical and hormonal profiles of FH-II and sporadic cases were similar. FH-III had a distinct phenotype, with higher PAC and higher frequency of hypokalemia (P < 0.001), and presented 45 years before sporadic cases. Nevertheless, the clinical and hormonal phenotypes of FH-IV and sporadic cases were similar, with the former being younger and having lower serum potassium levels. Conclusion In addition to being younger and having a family history of PA, FH-I and III share other typical characteristics. In this regard, FH-I is characterized by a low prevalence of hypokalemia and FH-III by a severe aldosterone excess causing hypokalemia in more than 85% of patients. The clinical and hormonal phenotype of type II and IV is similar to the sporadic cases.